2023
DOI: 10.3389/fnins.2023.1087950
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure results in brain region- and sex-specific changes in circHomer1 expression in adult mouse brain

Abstract: Circular RNAs (circRNAs) are a novel category of covalently-closed non-coding RNAs mainly derived from the back-splicing of exons or introns of protein-coding genes. In addition to their inherent high overall stability, circRNAs, have been shown to have strong functional effects on gene expression via a multitude of transcriptional and post-transcriptional mechanisms. Furthermore, circRNAs, appear to be particularly enriched in the brain and able to influence both prenatal development and postnatal brain funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Here we provide strong evidence that CREB, known to promote gene expression in a neuronal activitydependent pattern 39 , is a major positive regulator of circHomer1 biogenesis in neurons, affecting the transcription of Eif4a3 and Fus, genes coding RBPs that promote circHomer1 biogenesis 35,40 . We show that upstream of CREB, the ERK/MAPK and PKA pathways, which are crucial regulators of synaptic plasticity, are involved in the control of Eif4a3 and Fus expression and subsequently circHomer1 biogenesis.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Here we provide strong evidence that CREB, known to promote gene expression in a neuronal activitydependent pattern 39 , is a major positive regulator of circHomer1 biogenesis in neurons, affecting the transcription of Eif4a3 and Fus, genes coding RBPs that promote circHomer1 biogenesis 35,40 . We show that upstream of CREB, the ERK/MAPK and PKA pathways, which are crucial regulators of synaptic plasticity, are involved in the control of Eif4a3 and Fus expression and subsequently circHomer1 biogenesis.…”
Section: Introductionmentioning
confidence: 75%
“…We have previously shown that EIF4A3 can bind to circHomer1 and positively regulate its expression, identifying EIF4A3 as an upstream regulator of circHomer1 synthesis 35 . In addition, we recently showed that the imprinted lncRNA H19 , which has been previously shown to bind to EIF4A3 and obstruct its recruitment to downstream RNA targets, is a negative regulator of neuronal circHomer1 biogenesis and displays opposing developmental expression within the brain 40 . In order to identify additional factors that could modulate circHomer1 biogenesis, we searched the literature for RBPs enriched in the brain that could bind to EIF4A3 and have either been shown to or been predicted to bind to circHomer1 .…”
Section: Resultsmentioning
confidence: 99%